Prevalence of vitamin D deficiency in postmenopausal women and its association with fasting blood sugar - Sinha, Mridu; Goel, J. K.; Sah, Shanti; ., Akanshamani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vitamin D is indispensable for human body as it caters for both skeletal as well as extra-skeletal needs, especially in postmenopausal women. Aim of this study was to know the prevalence of vitamin D deficiency among apparent healthy postmenopausal women and to find its association with fasting blood sugar. Methods: This was a cross-sectional observational study of postmenopausal women attending Gynae OPD of Sri Ram Murti Smarak Institute of Medical Sciences, Bareilly, over a period of six months. Apparently healthy postmenopausal women were selected after satisfying inclusion-exclusion criteria and were subjected to fasting blood sugar and serum 25-hydroxy-vitamin D level. They were categorized as vitamin D deficient, insufficient or sufficient according to corresponding levels of <20ng/ml, 20-30ng/ml or >30ng/ml respectively. Upper reference level for fasting blood sugar was taken as 110mg/dl. Statistical analysis was done to see the association between vitamin D deficiency and fasting blood sugar. Results: Mean age of study group was 56.9 years and the average age of attainment of menopause was 50.3 years. Prevalence of vitamin D deficiency (57.4%) including insufficiency (13%) among postmenopausal women was high 70.4%, but there was no association between hypovitaminosis D and fasting blood sugar (p=0.949). Conclusions: Despite high prevalence of vitamin D deficiency among Indian postmenopausal women, there is no correlation between it and fasting blood sugar.